COLLABORATIVE GOVERNANCE DALAM UPAYA MENCIPTAKAN KETERTIBAN UMUM DAN KENTENTRAMAN MASYARAKAT DI KECAMATAN PUJUD KABUPATEN ROKAN HILIR TAHUN 2021-2022 - Hasani, Rijalul; Hadi, Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The emergence of various social problems such as criminal acts that hit Pujud District, Rokan Hilir Regency, proves that the crime rate has increased. The crime that often occurs in Pujud District is the distribution and abuse of crystal methamphetamine. On the other hand, this social phenomenon is a problem for society and the government. With the drug case in Pujud District, Rokan Hilir Regency, apart from disrupting security and order. This research aims to determine collaborative governance in an effort to create public order and public peace in Pujud District, Rokan Hilir Regency in 2021-2022. This research approach uses descriptive qualitative. Data collection techniques through interviews and documentation. There were seven research informants. The results of this research explain that collaborative governance in an effort to create public order and peace in the community needs to collaborate or cooperate by involving the local government, and the police chief as an assistant who participates, such as: (1). Face-to-face dialogue, this process is carried out within the framework of a meeting or deliberation with the parties involved. (2). Building trust, concludes that in the context of a meeting or deliberation to carry out a collaboration process, of course the government and various elements in society must build trust in the form of good cooperation. This will be beneficial for stakeholders. 3. Commitment to the process, that everyone must participate in creating good cooperation to be able to resolve existing problems. (4). Sharing understanding, which is done through socialization, or sharing information with each other. (5). Interim results are the results of a significant process to build momentum that can lead to successful collaboration. Keywords: Face-to-face dialogue, building trust, Commitment to the process, Sharing understanding, Interim results